Unsupervised Pattern Discovery in Automotive Time Series Pattern-based Construction of Representative Driving Cycles - Noering, Fabian Kai Dietrich; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2022)
In the last decade unsupervised pattern discovery in time series, i.e. the problem of finding recurrent similar subsequences in long multivariate time series without the need of querying subsequences, has earned more and more attention in research and industry. Pattern discovery was already successfully applied to various areas like seismology, medicine, robotics or music. Until now an application to automotive time series has not been investigated. This dissertation fills this desideratum by studying the special characteristics of vehicle sensor logs and proposing an appropriate approach for pattern discovery. To prove the benefit of pattern discovery methods in automotive applications, the algorithm is applied to construct representative driving cycles. About the author Fabian Kai Dietrich Noering is currently working in the technical development of Volkswagen AG as data scientist with a special interest in the analysis of time series regarding e.g. product optimization.
Introduction -- RelatedWork -- Development of Pattern Discovery Algorithms for Automotive Time Series -- Pattern-based Representative Cycles -- Evaluation -- Conclusion.
Keywords: Automotive engineering; Image processing$1 (BDigital techniques.s; Computer vision; Pattern recognition systems; Computer science; Automotive Engineering; Computer Imaging, Vision, Pattern Recognition and Graphics; Automated Pattern Recognition; Theory and Algorithms for Application Domains; Motor vehicle driving -- Mathematical models; Time-series analysis